Assessment of candidate high-grade serous ovarian carcinoma predisposition genes through integrated germline and tumour sequencing - Deepak N. Subramanian; Maia Zethoven; Kathleen I. Pishas; Evanny R. Marinović; Simone McInerny; Simone M. Rowley; Prue E. Allan; Lisa Devereux; Dane Cheasley; Paul A. James; Ian G. Campbell (npj Genomic Medicine)
Abstract High-grade serous ovarian carcinoma (HGSOC) has a significant hereditary component, only half of which is explained. Previously, we performed germline exome sequencing on BRCA1 and BRCA2-negative HGSOC patients, revealing three proposed and 43 novel candidate genes enriched with rare loss-of-function variants. For validation, we undertook case-control analyses using genomic data from disease-free controls. This confirms enrichment for nearly all previously identified genes. Additionally, one-hundred-and-eleven HGSOC tumours from variant carriers were sequenced alongside other complementary studies, seeking evidence of biallelic inactivation as supportive evidence. PALB2 and ATM validate as HGSOC predisposition genes, with 6/8 germline carrier tumours exhibiting biallelic inactivation accompanied by characteristic mutational signatures. Among candidate genes, only LLGL2 consistently shows biallelic inactivation and protein expression loss, supporting it as a novel HGSOC susceptibility gene. The remaining candidate genes fail to validate. Integrating case-control analyses with tumour sequencing is thus crucial for accurate gene discovery in familial cancer studies.